An Analysis of Teachers’ Difficulties Teaching Reading to Young Learners - Mohammad Fikri Nugraha Kholid; Mamluatul Mkaromah; Nunun Indrasari (Cipta Pustaka Nusantara, 2025)
This study investigates the challenges teachers encounter when teaching reading to young learners at SD N 2 Way Dadi. The research was prompted by observed difficulties in delivering effective reading instruction to early-grade students, with the primary aim of identifying and analyzing specific pedagogical obstacles. Grounded in Aryana and Apsara's theoretical framework, the study examines critical aspects of reading instruction including instructional media utilization, teaching strategies, material selection appropriateness, teaching technique efficacy, classroom conditions, textbook quality, and technological resource availability. These interconnected factors collectively influence reading instruction quality and were systematically explored through a descriptive qualitative methodology. Data collection employed in-depth interviews with English teachers and structured classroom observations, while analysis followed the Miles and Huberman model's three-stage process: data reduction, presentation, and conclusion drawing. Findings indicate that teachers face multifaceted challenges predominantly stemming from five key areas: limited access to suitable learning media, ineffective instructional strategies, suboptimal classroom environments, inadequate teaching materials, and insufficient technological support. These constraints collectively hinder optimal reading instruction delivery and student literacy development. The study's significance lies in its contextual examination of reading instruction barriers within a specific educational setting, contributing empirical evidence to the discourse on early literacy education. The identified challenges suggest urgent needs for: targeted teacher training programs, improved resource allocation, and strategic interventions to enhance reading pedagogy. These findings offer valuable insights for educational policymakers and school administrators seeking to improve early reading instruction outcomes. Furthermore, the research highlights potential areas for future studies, particularly regarding innovative solutions to resource limitations in developing educational contexts.